Penerapan Asuhan Keperawatan Demam Berdarah Dengue dalam Pemenuhan Kebutuhan Termoregulasi - Ratna Mahmud (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: a disease caused by dengue virus with clinical manifestations of fever, headache, hemorrhagic joint pain. Dengue hemorrhagic fever sufferers usually experience an increase in body temperature that exceeds normal limits which usually causes seizures. Method: used in this research is descriptive, with a case study approach taken in the dahlia room of a private hospital in Makassar city in July 2019. Data was obtained from the patient's mother, nurse, health team, progress notes, and health records. Result: After nursing action, body temperature returned to normal. Conclusion: from the hyperthermia treatment carried out in children with dengue hemorrhagic fever, it was found that the patient's hyperthermia could be resolved. the effect of administering fluid management on decreasing thermoregulation was developed